Influences of saltwater immersion on properties of wood-cellulosic paper. (13th February 2015) - Bunyaphiphat, Tunchira; Nakagawa-Izumi, Akiko; Enomae, Toshiharu
Abstract: The saltwater immersion method was developed to inhibit mould growth on flood- or tsunami-damaged paper. Commercially available fine paper used for printing and writing showed decreased tensile indices after saltwater immersion. The salt remaining in the paper tended to increase the moisture content because of the salt deliquescence and moisture in the air. The tensile index was restored by removing salt from the paper. Crystallization and distribution of salt in interfibre pores were also considered to influence interfibre rebonding. The difference in the fibre responses to saltwater depended on the relationship between nano-scaled pores in the fibre walls, osmotic pressure, and the degree of sizing, which resulted in low water retention values. More of the starch applied as a surface sizing agent was dissolved or dispersed during distilled water immersion than saltwater immersion. This loosened the fibre network, which was a factor that decreased the sizing degree of the paper.